ENDOTHELIAL NITRICOXIDE GENE POLYMORPHISMS IN IMPEDED BREAST CANCER TISSUE - HAYTHEM ALI ALSAYIGH (International Journal of Pharma and Bio Sciences, 2016)
The present study aims to investigate endothelial nitric oxide synthase (eNOS) gene polymorphisms in impeded breast cancer tissue, polymorphism detected using amplification VNTR flanking sequence by PCR, the results show significant differences between patients and control in the deletion sequence of intron 4 it was (33.33%) in patients and (12.5%) in control (odd ratio 3.7813 (CI%7.8857 - 1.8131), The present study concluded that deletion in VNTR sequence in eNOS gene associated with breast cancer disease.